Handbook of solid waste management austainability through circular economy - Baskar, Chinnappan; Ramakrishna, Seeram; Baskar, Shikha; Sharma, Rashmi; Chinnappan, Amutha; Sehrawat, Rashmi (Springer, 2020)
The issue and finding the green solution of Solid Waste Management are important challenges throughout the world. This book explores cutting edge developments in Circular Economy and Sustainability on Solid Waste Management, current research perspectives, existing problems on solid waste management system, industrial development and the latest green methodology for in Solid Waste conversion and regenerate products and materials, environmental solutions, social awareness and development on solid waste management and the future perspectives of Circular Economy for industrial revolution 4.0 with the mission of green chemistry and engineering on solid waste management. The book focuses on chapters from different researchers, faculty members, scientists and engineers, industrialist and experts from different countries working on the Circular Economy on Solid Waste Management. It also features the importance of integration of multi-disciplinary research fields on Circular Economy for Sustainable Development. It provides latest development in and current research perspectives, technology development, and critical thinking and societal requirements and development on Circular Economy of Solid Waste Management to researchers, scientists, engineers, environmental managers, policy makers, and Experts of Energy Division of Government and Private Organization and Industries.